Agronomic performance and multivariate analysis in green chive production in response to irrigation depths and synthetic fertilization levels (Research, Society and Development, 2020)
This work aimed to evaluate the development of green chive in detriment to the irrigation blade and synthetic fertilization. The experiment was conducted in the experimental area of Arapiraca Campus of UFAL. The experimental design had a 5 x 6 factorial, in DBC, with four blocks, the treatments adopted were five irrigation blades and six levels of NPK fertilization. The data obtained were subjected to analysis of variance, of regression and multivariate: principal component analysis (PCA) and cluster hierarchical analysis (CHA), using the statistical software R. The results show that excessive blades and fertilizers limit the growth and productivity of the green chive crop. The best interactions between blades and the NPK are between the 100% and 125% ETc and 100% and the recommended 150% fertilization intervals. The ACP showed that the levels of fertilization NPK A3 and A4 in the blades were the ones that most influenced the variables related to the culture of green chive. The variables of major commercial interest determine the major part of the NPK level variability in irrigation blades. AHC indicated the height of the plant with greater dissimilarity between the other variables and the variables diameter and number of bulbs with greater similarity. Interactions L4A6 and L5A6 have the largest similarity and L3A3 the largest dissimilarity between the others. The L3A3 interaction showed the highest number of variables, with no response of any variable for the interaction with the L4 blade and for the A1 and A2 fertilizers.